Efektivitas Proses Rekrutmen Guru dalam Meningkatkan Kualitas Pendidikan - Nurisma, Anggis Rahma; Cahyani, Annisa Amelia; Aini, Amanda Sefrilisa; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (TSAQOFAH, 2024)
The purpose of this research is to understand the teacher recruitment process at SMPN 47 Surabaya and its impact on improving the quality of education at SMPN 47 Surabaya. This type of research is using descriptive qualitative research, which is a research procedure carried out by producing descriptive data in the form of written or spoken words from someone who is observed. Based on the results of this study, it shows that the implementation of the recruitment of teaching staff (teachers) in SMPN 47 Surabaya is carried out or submitted to the education office, where each level of education such as elementary, junior high, state high school will be submitted to the education office. Recruitment of teaching staff (Teachers) before being submitted to the education office, the first stage carried out by the school is to analyze the needs required. After analyzing the school will report the shortage of educators to the education office, and then the education office will conduct selections such as PNS tests, or PPPK tests. The test aims to get employees who have certain technical competencies and are professionally certified in order to improve the quality of education.